Physical & Chemical Composition Nutritional Evaluation and Efficiency Tests of Broiler on Various Types of Diets: Investigating the Composition and Impact of Diets on Broiler Poultry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Poultry meat and eggs are a great source of vitamins micro nutrients that add to human diet as a valuable portion. it is an attempt to study the physical and chemical evaluation of poultry rations mainly different physical forms of compounded feeds and to study the chemical composition of poultry rations. Broiler meat has a greater market relative to other foods, mainly due to the disadvantages of beef and pork, and religious uses. This also holds the highest acceptability of all customer pieces. The excess feeding is transformed into food encouraging broiler chickens to provide an infinite supply of feed would contribute to the need to consume excess poultry. The manufacture of lean poultry meat to satisfy consumer demands is thus a big industry priority.